PENGARUH FINANCIAL TECHNOLOGY (FINTECH) TERHADAP KINERJA UMKM MELALUI MEDIASI AKSES KEUANGAN DI PROVINSI JAWA TENGAH, INDONESIA - Amelia Sholeha; Anisa Sains Kharisma (Jurnal Bina Bangsa Ekonomika, 2024)
This study examines the impact of financial access mediation through financial technology on the performance of SMEs in Central Java Province, Indonesia. This study collected 100 SME respondents who had used services on fintech applications, to find out how these financial technology innovations affected SME business performance. The PLS-SEM model was used to test the proposed hypothesis. The results of the study show that the relationship between fintech and access to finance is positive and significant. These findings also reveal that fintech has a positive and significant effect on the performance of SMEs. In addition, the results of further research show that access to financing mediates the relationship between fintech services and SME performance positively and significantly. Therefore, this study concludes that access to financing is an important mechanism in the influence of fintech services on the operational and financial performance of SMEs. The study provides a better understanding of how SMEs can improve their performance by leveraging fintech as a solution to obtain new sources of funding